Islamic Jurisprudence Study in Religious Life Development in Pasilambena Subdistrict, Selayar Islands Regency (Group Communication Overview) - Muhammad Arpin; Arifuddin Tike; Kamaluddin Tajibu (Jurnal Mercusuar, 2023)
The main issue in this journal is the study of Islamic jurisprudence (fikih) in fostering religious life in Pasilambena District, Kepulauan Selayar Regency, with a focus on group communication. This research emphasizes aspects such as group communication models, group communication activities, and factors supporting and hindering group communication. To address the research problem, a qualitative research model with four approaches was chosen, namely communication approach, sociological approach, pedagogical approach, and normative approach. The data collection method involves primary data sources and supporting data (secondary) through library research using books, magazines, and field research through observation, interviews, and documentation. The research instruments include a list of questions (interview guidelines), a laptop, camera, recording tools, notebooks, and pens. Data processing and analysis are conducted in three stages: data reduction, data presentation, and drawing conclusions. The aim of this research is to realize a substantive, moderate, and enlightening religious life. Group communication analysis is conducted through the development of Islamic jurisprudence studies based on faith, worship, and morality, with an approach of mutual understanding, mutual understanding, and mutual assistance through forums/lectures, discussions/dialogues, and demonstrations/practices, with the application of wisdom and good teaching, in accordance with the authentic Islamic values from the Quran and Hadith. The research results indicate the importance of group communication models in accelerating and facilitating the understanding of noble Islamic values, thus creating a conducive religious life in Pasilambena District, Kepulauan Selayar Regency. Group communication activities also play a significant role in disseminating correct religious understanding, in line with Islamic values, resulting in a complete religious life in Pasilambena District, Kepulauan Selayar Regency.